Meta-Juridical Analysis on the Legal Arguments beyond Changes in Indonesian’s Marriage Age Rule - Ahmad Dakhoir; Sri Lumatus Sa’adah (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
This paper examines then criticizes legal arguments beyond the change in marriage age minimum limit in Indonesian case then proposing a new insight fur future regularion. It is a normative research with a meta-juridical approach. The primary data is Law Number 16 of 2019 and the SIPP (Sistem Informasi Penelusuran Perkara) report of the Supreme Court of the Republic of Indonesia analyzed using content analysis techniques. The results suggest that the legal argument for changing the minimum age limit for marriage as referred to in Article 7 of Law Number 16 of 2019 was motivated by assumption on the loss of women's rights, the increasing number of child marriage cases, and global pressures. From the perspective of a meta-juridical approach, the three factors are not appropriate arguments for changing the minimum age limit for marriage. On the contrary to the purpose beyond the change, the Article 7 of Law Number 16 of 2019 has rather caused the increasing child marriage after its issuance. Therefore, it is suggested that the standard for determining marriage age limit in the future regulation also considers the concept of of bâ’ah, ‘âqil, and bâligh which combine biological maturity and social responsibility.